Working alliance among mental health nurses in Indonesia: A comparative analysis of socio-demographic characteristics - Iyus Yosep (Belitung Raya Foundation, 2021)
Background: Working alliance between therapist and client in psychotherapy practice has become proven to compensate for a significant difference in various psychotherapy modalities. However, few studies have investigated the structure of alliance in the context of nurses working at mental health hospitals in Indonesia.